2014
DOI: 10.1136/bmj.g1888
|View full text |Cite|
|
Sign up to set email alerts
|

Antidepressant efficacy of agomelatine: meta-analysis of published and unpublished studies

Abstract: Objective To systematically review published and unpublished efficacy studies of agomelatine in people with depression.Design Systematic review and meta-analysis. Eligibility criteria Double blind randomised placebo and comparator controlled trials of agomelatine in depression with standard depression rating scales. Data sourcesData synthesis Studies were pooled by using a random effects model with DerSimonian and Laird weights for comparisons with placebo and comparator antidepressant. The primary efficacy me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
100
1
15

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(133 citation statements)
references
References 46 publications
12
100
1
15
Order By: Relevance
“…36 Among patients with severe depression, the SMD of 0.61 clearly separates SSRIs from placebo, and this can be considered a clinically important reduction in depressive symptoms, as measured by the HAM-D; however, this result is difficult to achieve with antidepressant treatment for MDD. 36,37 According to the previous metaanalyses of agomelatine, which was also recently approved for the treatment of MDD, the SMDs were 0.18-0.26 38,39 ; these results are similar to those of the present meta-analysis.…”
Section: Discussionsupporting
confidence: 81%
“…36 Among patients with severe depression, the SMD of 0.61 clearly separates SSRIs from placebo, and this can be considered a clinically important reduction in depressive symptoms, as measured by the HAM-D; however, this result is difficult to achieve with antidepressant treatment for MDD. 36,37 According to the previous metaanalyses of agomelatine, which was also recently approved for the treatment of MDD, the SMDs were 0.18-0.26 38,39 ; these results are similar to those of the present meta-analysis.…”
Section: Discussionsupporting
confidence: 81%
“…In the first, vortioxetine was found to be superior in efficacy to agomelatine [30]. While these results are interesting, they are limited by the fact that agomelatine is not available in North America and is considered to be only a modestly effective agent [51]. More promising are the results from the second active comparator trial that demonstrated non-inferiority of vortioxetine versus venlafaxine, a commonly used SNRI [31].…”
Section: Vortioxetinementioning
confidence: 54%
“…A variety of more traditional antiinflammatory therapies has also been used for the treatment of depression, including aspirin and other nonsteroidal antiinflammatory drugs, statins, and cytokine inhibitors like etanercept (which blocks TNF) [92][93][94][95]. Agomelatine is a a b c d member of a novel class of new antidepressants which are melatonin agonists; it has been approved by the European Union, after being shown to have similar efficacy to SSRIs for the treatment of depression [96,97]. Melatonin agonists have numerous effects on the immune system, most of which serve to limit inflammation [98].…”
Section: Therapeutic Approaches To the Treatment Of Depression: A Focmentioning
confidence: 99%